Computational Biology: A Hypertextbook - Scott T Kelley (ASM Press, 2018)
1. BLAST 2. Protein Analysis 3. Sequence Alignment 4. Patterns in the Data 5. RNA Structure Prediction 6. Phylogenetics 7. Probability: All Mutations are not Equal (-ly Probable) 8. Bioinformatics Programming: A Primer